Everyday Politics and the Leadership of Health Policy Implementation. Issue 3 (2nd July 2016) - Gilson, Lucy
Abstract: This article aims to prompt reflection about the everyday politics of health systems, their importance to health policy implementation, and what sort of leadership, provided by whom, is required to address them. It is founded on insights drawn from empirical and theoretical literature, combined with practical experience developed through relevant research and teaching. Ultimately it argues that the everyday politics of the health system represent the multiple actors, interests, and choices that frontline leaders routinely address and that influence the collective action taken through the system in pursuit of public value. Leadership to address these everyday politics entails the practice of power and support for collective sense-making. Nurturing these political leadership skills through new forms of leadership development is therefore a vital component of health system development.